2006
DOI: 10.1094/phyto-96-0137
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Phylogenetic Relationships, and Specific Detection of Peach mosaic virus

Abstract: Peach mosaic virus (PcMV) and Cherry mottle leaf virus (CMLV) are serologically related viruses that cause distinct diseases, have a different host range, and are vectored by different eriophyid mites. Sequence analysis of the genome of PcMV indicates that it is closely related genetically to CMLV but distinct, with similar genome organization and a member of the genus Trichovirus. The genome of PcMV consists of 7,988 nucleotides, excluding a poly(A) tail at the 3' end of the genome. Four putative open reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Similar proteins are found in some, but not all, viruses in the genus Trichovirus (54). It was recently shown that the nucleic acid-binding protein of GVA is able to suppress RNA silencing (127), suggesting that this function may be conserved in other related proteins of flexiviruses.…”
Section: -Proximal Orfs Encoding Capsid and Other Proteinsmentioning
confidence: 69%
“…Similar proteins are found in some, but not all, viruses in the genus Trichovirus (54). It was recently shown that the nucleic acid-binding protein of GVA is able to suppress RNA silencing (127), suggesting that this function may be conserved in other related proteins of flexiviruses.…”
Section: -Proximal Orfs Encoding Capsid and Other Proteinsmentioning
confidence: 69%
“…CMLV is taxonomically and serologically related to PcMoV [7]. In contrast, the intergenic region between ORFs 3 and 4 is more closely related to that of CMLV-SA1162-21 (77 % identity) than to that of PcMoV (48 % identity).…”
mentioning
confidence: 99%
“…The PcMV-specific fragments were amplified making this protocol to be very useful for specific detection of this virus (Fig. 2.7) (James et al 2006).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%